Political economy or economic politics? Prospects of civil society in era of globalisation - Elsenhans, Hartmut (2000)
The author develops an argument that the theoretical and historical foundations of International Political Economy (IPE), as defined in most of the Anglo-Saxon literature, are too narrow to cope with the challenges of globalisation, and are based on perspectives of mainstream economics which may potentially discount the political component of IPE. He shows that IPE, as it is actually practised, has a pre-Keynesian economic approach which does not allow for distinction between profit and rent - which is a major distinction for patterns of behaviour and social integration in societies - and constitutes an essential link between purely economic and political-economic areas of investigation. He argues that due to its pre-Keynesian approach, IPE privileges actor-centered approaches without sufficiently investigating the malleability of structures and hence also the effects of the strategies of actors on global, national and local economic structures, which may be important for the dynamics of the global system. To illustrate his case, he analyses his political-economic foundations of autonomy of civil society (CS) and emergence of profit as opposed to rent in his bid to characterise the international system as being only partially capitalist, with essential areas dominated by rent appropriation and power, which are on the rise due to globalisation. According to him, the uncivilised aspect of the international system is not compensated by growth of transnational interactions, often characterised by the notion of an emerging international CS. The literature frequently refers to the rapid growth of transnationally operating or even transnationally organised NGOs, but argues that these do not have the material basis of an autonomous CS at their disposal. He concludes with the perspective of an extension of capitalist (by necessity, welfarist) structures to the South which allow for a strengthening of profit against rent and make globalisation socially acceptable. - Reproduced
Keywords: Economics; Civil society; Globalization